Alternated mRNA expression of the genes in chromosome 9p21 is associated with coronary heart disease and genetic variants in chromosome 9p21. Issue 178 (June 2019) - Zhou, Liting; Zheng, Dongchun; Song, Xinyue; Zhu, Jian; Qi, Wen; Ding, Shuang; Zhang, Yuezhu; Xu, Qi; Han, Xu; Zhao, Yaming; Zhao, Tianyang; Guo, Shuangyu; et al.
Highlights: Lower mRNA levels of CDKN2A and CDKN2B, as well as higher mRNA level of MTAP may be related to CHD. Rs2383207 may affect the occurrence of CHD by influencing the patients'CDKN2A mRNA expression level. ANRIL may not be related to the occurrence of CHD in Chinese Han population.